Pengaruh Kompetensi Sumber Daya Manusia, Komitmen Organisasi, dan Kepemimpinan Terhadap Akuntabilitas Pengelolaan Dana: (Studi Kasus Pada BUMDes Se-Kecamatan Dawan) - Cahayani, Tata Intan; Indraswarawati, Sang Ayu Putu Arie; Muliati, Ni Ketut (UNHI Press, 2025)
Accountability for fund management is closely related to financial reporting, so it is necessary to implement good accountability in order to share accurate and accountable information for interested parties. The purpose of this study was to determine the effect of human resource competence, organizational commitment, and leadership on fund management accountability in BUMDes Se-Kecamatan Dawan using a quantitative approach. The population of this study amounted to 101 managers of BUMDes Se-Kecamatan Dawan. By choosing purposive sampling technique, it was found that the sample of this study amounted to 33 respondents consisting of directors, secretaries, treasurers, and heads of business units in BUMDes. The data analysis technique consists of descriptive statistical analysis, research instrument test, classical assumption test, multiple linear regression analysis, and model feasibility test using the IBM SPSS V.23 application. The findings of this study show that the variables of human resource competence, organizational commitment, and leadership partially affect the accountability variable of fund management.